Altitude‐mediated soil properties, not geography or climatic distance, explain the distribution of a tropical endemic herb. Issue 2 (9th February 2022) - Moutouama, Jacob K.; Gaoue, Orou G.
Abstract: Understanding the ecological processes that govern species' range margins is a fundamental question in ecology with practical implications in conservation biology. The center‐periphery hypothesis predicts that organisms have higher abundance at the center of their geographic range. However, most tests of this hypothesis often used raster data, assuming that climatic conditions are consistent across one square km. This assumption is not always justified, particularly for mountainous species for which climatic conditions can vary widely across a small spatial scale. Previous studies rarely evenly sample occurrence data across the species' distribution. In this study, we sampled an endemic perennial herb, Thunbergia atacorensis (Acanthanceae), throughout its range in West Africa using 54 plots and collected data on (a)biotic variables, the species density, leaf mass per area, and basal diameter. We built a structural equation model to test the direct and indirect effects of distance from geographic and climatic niche centers, and altitude on Thunbergia density as mediated by abiotic and biotic factors, population demographic structure, and individual size. Contrary to the prediction of the center‐periphery hypothesis, we found no significant effect of distance from geographic or climatic niche centers on plant density. This indicates that even the climatic center does not necessarily have optimal ecological conditions. In contrast, plant density varied with altitudinal gradient, but this was mediated by the effect of soil nitrogen and potassium which had positive effect on plant size. Surprisingly, we found no direct or mediating effect of interspecific competition on plant density. Altogether, our results highlight the role of geography, climatic, and ecological mismatch in predicting species distribution. Our study highlights that where altitudinal gradient is strong local‐scale heterogeneity in abiotic factors can play important role in shaping species range limits. Abstract : We tested the center‐periphery hypothesis in Thunbergia atacorensis, a range‐limited species and find that plant abundance did not vary with distance from geographic or climatic niche center but decreased with altitude indicating that even climatic centers do not necessarily have optimal ecological conditions. Our study highlights the relative role that abiotic factors play in shaping species range limits and the critical role of altitudinal gradient. Our findings further suggest that to understand range limitation, one must look beyond plant abundance and consider alternative responses such as plant demography and population dynamics.